Penerapan Model Pembelajaran Kooperatif Team Games Tournament dengan Media Canva sebagai Upaya Meningkatkan Hasil Belajar Bahasa Arab Siswa kelas X MA YPPA Cipulus - Lina L; TB Abdul Hamid (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Arabic Language learning at Madrasah Aliyah level still faces various constraints, especially low student learning performance caused by lack of motivation, minimal vocabulary mastery, as well as teaching methods that tend to be monotonous and teacher-centered. Therefore, innovative learning strategies are required that suit the characteristics of 21st century students.This study aims to improve students’ Arabic Language learning activities and outcomes through the application of Canva’s media-assisted Team Games Tournament (TGT)-type cooperative learning model. The study used Classroom Action Research (CRA) method implemented in MA YPPA Cipulus on class X students numbering 35 people. Research was conducted in two cycles with planning, action, observation, and reflection stages. Data were collected through observation, testing learning outcomes, and documentation. Data analysis was conducted both qualitatively and quantitatively. The results of the study showed that the application of Canva-assisted TGT was able to increase students’ learning activity from 70% in cycle I to 93% in cycle II. Additionally, students’ learning outcomes also improved significantly, with the percentage of learning dropouts from 14% in pre-cycle, to 71% in cycle I, and reaching 91% in cycle II. Students’ mean scores increased from 43 in the pre-cycle, to 73 in cycle I, and 89 in cycle II.